Prevalence of gastric precancerous lesions in Ardabil, a high incidence province for gastric adenocarcinoma in the northwest of Iran - Malekzadeh, R (Copyright 2004 Journal of Clinical Pathology, 2004)
Background/Aims: Ardabil Province, in northwestern Iran, has the highest rate of gastric (predominantly cardia) adenocarcinoma in Iran. This study aimed to investigate the feasibility of endoscopic screening and to look for associated Helicobacter pylori infection and gastric precancerous lesions. Methods: One thousand one hundred and five adult volunteers, residents of Ardabil and Meshkinshahr, districts, 40 years old and above were selected and invited by a simple random household canvass in rural and urban locations. Informed consents were obtained and upper gastrointestinal video endoscopy was performed to biopsy all visible lesions and standard sites in the antrum, corpus, and cardia Results: One thousand and eleven of the invited individuals agreed to participate, including 494 men and 517 women, with a mean (SD) age of 53.32 (10.39) years. Endoscopy was well tolerated by all subjects; 96.7% of antral and 80.7% of cardia mucosal biopsies were satisfactory. The urease test or histology for H pylori was positive in at least 89.2% of subjects. Histological evidence of mucosal atrophy was seen in 39.3% of antral and 21.9% of cardia samples. Chronic gastritis with or without activity, reactive atypia of glandular epithelium, intestinal metaplasia, dysplasia, and cancer were found in 95.1%, 38.0%, 8.7%, 0.2%, and 0.3% of antral and 85.3%, 22.9%, 3.8%, 0.3%, and 0.1% of cardiac biopsies, respectively. Conclusion: Endoscopic screening for upper gastrointestinal diseases was feasible and well tolerated in Ardabil, Iran. Most subjects showed H pylori infection. Atrophic gastritis, reactive atypia, and intestinal metaplasia were common in antrum, corpus, and cardia subsites.